Evolving DevOps Practices in Modern Software Engineering: Trends, Challenges, and Impacts on Quality and Delivery Performance - Zumhur Alamin; Dahlan; Khaeruddin; Sahrul Ramadhan (Ran Edu Center, 2025)
The adoption of DevOps has significantly reshaped modern software engineering by tightly integrating development and operations activities to achieve faster, more reliable, and scalable software delivery. Despite widespread industry adoption, empirical research on the quantifiable impact of DevOps practices remains fragmented. This study aims to investigate how contemporary DevOps practices influence software quality, delivery speed, and team productivity in real-world environments. A mixed-method approach was employed, combining a multi-case study across four mid-to-large enterprises with a controlled simulation of key DevOps performance metrics. Data were collected from interviews, DevOps telemetry tools (e.g., Jenkins, GitLab CI/CD, Docker, and Kubernetes), and automated system logs. The findings indicate that mature DevOps adoption is associated with a 45% increase in deployment frequency, a 38% reduction in lead time for changes, and a 32% decrease in change failure rates. Nonetheless, organizations face persistent challenges in integrating security (DevSecOps), managing technical debt, and fostering cultural alignment across siloed teams. The results confirm the strategic importance of Infrastructure as Code (IaC), continuous monitoring, and automated testing in optimizing DevOps outcomes. For practitioners, this study offers a practical roadmap for scalable and sustainable DevOps transformation. For researchers, it identifies critical gaps in socio-technical integration and intelligent automation that warrant further investigation. This research contributes to bridging empirical evidence and theoretical frameworks in the evolving field of DevOps in software engineering.